A Neural Circuit from the Paraventricular Thalamus to the Bed Nucleus of the Stria Terminalis for the Regulation of States of Consciousness during Sevoflurane Anesthesia in Mice. (9th March 2022) - Li, Jia-Yan; Gao, Shao-Jie; Li, Ran-Ran; Wang, Wei; Sun, Jia; Zhang, Long-Qing; Wu, Jia-Yi; Liu, Dai-Qiang; Zhang, Pei; Tian, Bo; Mei, Wei
Abstract : Background: The neural circuitry underlying sevoflurane-induced modulation of consciousness is poorly understood. This study hypothesized that the paraventricular thalamus bed nucleus of the stria terminalis pathway plays an important role in regulating states of consciousness during sevoflurane anesthesia. Methods: Rabies virus–based transsynaptic tracing techniques were employed to reveal the neural pathway from the paraventricular thalamus to the bed nucleus of the stria terminalis. This study investigated the role of this pathway in sevoflurane anesthesia induction, maintenance, and emergence using chemogenetic and optogenetic methods combined with cortical electroencephalogram recordings. Both male and female mice were used in this study. Results: Both γ-aminobutyric acid–mediated and glutamatergic neurons in the bed nucleus of the stria terminalis receive paraventricular thalamus glutamatergic projections. Chemogenetic inhibition of paraventricular thalamus glutamatergic neurons prolonged the sevoflurane anesthesia emergence time (mean ± SD, hM4D–clozapine N -oxide vs. mCherry–clozapine N -oxide, 281 ± 88 vs. 172 ± 48 s, P < 0.001, n = 24) and decreased the induction time (101 ± 32 vs. 136 ± 34 s, P = 0.002, n = 24), as well as the EC5 0 for the loss or recovery of the righting reflex under sevoflurane anesthesia (mean [95% CI] for the concentration at which 50% of the mice lost their righting reflex, 1.16 [1.12 to 1.20] vs . 1.49 [1.46 to 1.53] vol%, P < 0.001, n = 20; and for the concentration at which 50% of the mice recovered their righting reflex, 0.95 [0.86 to 1.03] vs. 1.34 [1.29 to 1.40] vol%, P < 0.001, n = 20). Similar results were observed during suppression of the paraventricular thalamus bed nucleus–stria terminalis pathway. Optogenetic activation of this pathway produced the opposite effects. Additionally, transient stimulation of this pathway efficiently induced behavioral arousal during continuous steady-state general anesthesia with sevoflurane and reduced the depth of anesthesia during sevoflurane-induced burst suppression. Conclusions: In mice, axonal projections from the paraventricular thalamic neurons to the bed nucleus of the stria terminalis contribute to regulating states of consciousness during sevoflurane anesthesia. Abstract : Chemogenetic inhibition of paraventricular glutamatergic neurons in the mouse thalamus projecting to the bed nucleus of the stria terminalis reduced induction time and prolonged emergence from sevoflurane anesthesia, while activation of this pathway had opposite effects. These observations suggest that glutamatergic neurons of the paraventricular thalamus contribute to the mechanisms of actions of sevoflurane anesthesia via their projections to the bed nucleus of the stria terminalis.